Fracture Resistance of Simulated Immature Teeth Filled with Three Types of Calcium Silicate Cement after Intracanal Medication with Ca(OH)2: An Ex Vivo Study - Kuttalee Sriprasart; Suwit Wimonchit (Hindawi Limited, 2024)
Objectives. The aim of this study was to evaluate the 1-day fracture resistance of simulated immature teeth with an apical plug with ProRoot MTA, MTA Angelus, and RetroMTA after calcium hydroxide intracanal medication. Materials and Methods. Sixty extracted, single-rooted human mandibular premolars were randomly divided into six groups of 10 teeth each. Firstly, to standardize the 9 mm root length, the crowns were cut off at and 9 mm below the cementoenamel junction transversely. Simulations for immature apices were carried out by using No. 1-6 Peeso reamers to pass through the apex to obtain a diameter of 1.7 mm at the apical opening. One group served as a negative control without any treatment, while the other groups received 30 days of calcium hydroxide intracanal medication. Four groups were plugs with 4 mm of ProRoot MTA, MTA Angelus, RetroMTA, and gutta-percha, respectively. The last one was served as a positive control group without filling inside. After 1 day of incubation, specimens were vertically loaded in a universal testing machine at a crosshead speed of 1 mm/min until fracture occurred. The peak load to fracture (Newton) and fracture pattern were recorded. A one-way analysis of variance (ANOVA) followed by Tukey's HSD test was used for data analysis. Results. The highest mean load to fracture was shown in the negative control group (543.33 ± 37.17 N), followed by ProRoot MTA (432.82 ± 68.06 N), MTA Angelus (396.92 ± 59.93 N), RetroMTA (389.08 ± 56.25 N), and gutta-percha (283.28 ± 43.40 N), and the lowest belonged to the positive control group (239.98 ± 27.19 N). The significant differences were found between both the control and experimental groups with an apical plug with calcium silicate cement (p <0.05). There were no significant differences among those three apical plugs (p >0.05). Conclusion. Apical plugs with ProRoot MTA, MTA Angelus, and RetroMTA had an immediate strengthening effect on simulated immature teeth after calcium hydroxide intracanal medication had been used.